Regeneration of accessions in seed collections: A decision guide - Sackville-Hamilton, N. Ruaraidh; Chorlton, K.H. (1997)
This decision guide is intended to facilitate the development of optimum procedures for regeneration of seed germplasm. It deals with the timely identification of accessions with inadequate quality or quantity of seed, and considers the regeneration of those accessions to produce new seed of maximum quality and optimum quantity, with minimum loss of genetic integrity and as cost-effectively as possible.